1995
DOI: 10.1002/tl.37219956106
|View full text |Cite
|
Sign up to set email alerts
|

Increasing minority students' success in calculus

Abstract: The Academic Excellence Workship demonstrates that achievement of underrepresented minority students in mathematics and subsequent persistence in SME majors may be associated less with precollege ability than with in‐college academic experiences and expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Perhaps due to the collective identity fostered through the years of living and learning together, the horizontal network that involves study groups and a collaborative environment is strong. The ability to utilize others' knowledge bases and create links through this network is critical for success as having a strong skill set and mastery of course content enhances student confidence and success (Astin & Astin, 1992; Bonsangue & Drew, 1995; Springer & Springer, 1999; Treisman, 1992). This resonates with the quantitative study of the program which reported that students rated study groups as one of the most beneficial aspects of the program (Maton et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps due to the collective identity fostered through the years of living and learning together, the horizontal network that involves study groups and a collaborative environment is strong. The ability to utilize others' knowledge bases and create links through this network is critical for success as having a strong skill set and mastery of course content enhances student confidence and success (Astin & Astin, 1992; Bonsangue & Drew, 1995; Springer & Springer, 1999; Treisman, 1992). This resonates with the quantitative study of the program which reported that students rated study groups as one of the most beneficial aspects of the program (Maton et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The second area concerns student understanding of the foundational concepts and their development of critical abilities essential for achievement (Astin & Astin, 1992; Bonsangue & Drew, 1995; Springer, Stanne & Donovan, 1999; Treisman, 1992; Barlow & Villarejo, 2004). To promote knowledge and skill development it is critical that the concepts necessary for mastery are explicit (Bennet et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While there have been academic gains documented for students participating in PLTL and similar programs (Bonsangue & Drew, 1995;Cohen, 1997;Freeman, 1995Freeman, , 1997Fullilove, Fullilove, Terris, & Lacayo, 1988;Gosser, Cracolice, Kampmeier, Roth, Strozak, & Varma-Nelson, 2001;McCaffrey & Meyers, 1992;Treisman, 1992), it is the facilitators who, as peer mentors, may experience the most significant gains. Webb, Farivar, and Mastergeorge (2002) posited that in a peer-learning situation, it is not just the student receiving the explanation, but also the student offering it, who benefits.…”
Section: Introductionmentioning
confidence: 96%
“…These minority students in freshman calculus courses were invited to attend collaborative workshops. Bonsangue (1994; Bonsangue & Drew, 1995) found that the minority students in the workshop achieved significantly higher grades in the calculus course than did the minority students not enrolled in the workshop. When compared to nonminority students, there was no statistically significant difference in their grades.…”
Section: Introductionmentioning
confidence: 98%